Biting myself so I don’t bite the dust: prevalence and predictors of deliberate self-harm and suicide ideation in Azorean youths - Carvalho, Célia Barreto (2017)
To characterize non-suicidal self-injury (NSSI) behaviors, methods, and functions as well as suicide ideation in the adolescent population of a Portuguese community in São Miguel Island, Azores. Increasing rates of NSSI behaviors among adolescents have been observed globally, while suicidal behavior has been pointed as a major cause of death during adolescence.